Student worksheets (LKPD) using a scientific approach: the impact on critical thinking skills in linear equation system material - Lovyantika, Christin; Marzal, Jefri; Haryanto, Haryanto (Universitas Islam Negeri Raden Intan Lampung, 2021)
The LKPD development process with a scientific approach uses the ADDIE model which consists of several stages, the first is analysis, namely analyzing the curriculum, validating work gaps, analyzing student needs and characteristics, the second stage is development, namely small group trials and large group trials. The third stage is implementation is by applying the LKPD that has been tested and the last stage is an evaluation which conducts an assessment of the comments of teachers and students on the developed LKPD. The purpose of this development research is to determine the effectiveness of mathematics LKPD with a scientific approach on SPTLT material. The effectiveness obtained based on the developed product can improve students' critical thinking skills from the results of the pretest and posttest which were tested with the N-gain test. After being analyzed by the N-gain test, a score of 0.73 is obtained, namely in the high category and the LKPD developed is effective. LKPD with this scientific approach can improve students' critical thinking skills very well.